Attractiveness and competitiveness of irradiated light brown apple moths. Issue 3 (30th July 2013) - Stringer, Lloyd D.; Sullivan, Nicola J.; Sullivan, Thomas E.S.; Mitchell, Vanessa J.; Manning, Lee‐Anne M.; Mas, Flore; Hood‐Nowotny, Rebecca Clare; Suckling, David Maxwell
Abstract The sterile insect technique (SIT) potentially provides a socially acceptable approach for insect eradication of new pest incursions. The light brown apple moth, Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae), was discovered in Berkeley (CA, USA) in 2006, leading to an incursion response that included this technology. In this study, we assessed factors affecting mating success from a bisex release of irradiated moths: effects of radiation dose on male multiple mating, male flight competition, female sex pheromone titre and attractiveness of irradiated females to males, and identification of successful mating in vineyards of either irradiated or wild males (identified by isotope analysis of spermatophores from sentinel females). There was a significant negative relationship between male radiation dose and mating frequency. In head‐to‐head flights of irradiated males against non‐irradiated males to a pheromone lure in a wind tunnel, irradiated males reached the lure first only 31% of the time. With increasing radiation dose, the production of the major sex pheromone component in females, (E)‐11‐tetradecenyl acetate, dropped, from 0.7 ± 0.1 ng per female in non‐irradiated females to 0.2 ± 0.07 ng per female when irradiated at 300 Gy. Male catch was reduced to 11% of control females in traps containing females irradiated at 300 Gy. Isotope analysis of spermatophores found in the bursa copulatrix of females indicated that mating success of irradiated males inside the live (entry‐only) traps containing virgin females was lower (13.1 ± 3.3%) than suggested by male catch (21.2 ± 3.8%) in pheromone traps, the current standard for assessing field competitiveness. Impacts of irradiation on male and female moth fitness should be taken into account to improve estimates of irradiated to wild male E. postvittana overflooding ratios needed for population suppression.